Analisis Strategi Penghimpunan Zakat, Infaq dan Dana Sosial Pada KBMT Dana Akhirat Arjasari Banjaran Bandung - Agustini Solihatin; Rima Elya Dasuki; Nanang Sobarna (Program Studi Ekonomi Syariah Institut Manajemen Koperasi Indonesia, 2021)
Collection of zakat, infaq and social funds is one of the social functions that exist in sharia cooperatives. Efforts that can be made to implement social functions in sharia cooperatives must of course have a good collection, so that they are distributed in accordance with what is prescribed by Islam and all people in need can feel the maximum benefits from sharia cooperatives. In addition, the surrounding community can entrust or set aside some of their more opinion for zakat, infaq and social funds which will be redistributed by sharia cooperatives to people who are entitled to receive them with full trust. With that, the purpose of this study is to find out the description of the collection strategy and the opportunities and challenges in collecting zakat, infaq, and social funds in KBMT Dana Akhirat Arjasari Banjaran Bandung. The research method used is a case study with descriptive data analysis with a qualitative approach which can be obtained through informants and documents with data collection techniques through observation, interviews, and literature studies to be able to describe the collection and opportunities as well as challenges in collecting zakat, infaq and social funds. The results of the research on the analysis of strategies for collecting zakat, infaq and social funds that were carried out were in accordance with Islamic law but still optimized from internal parties and still did not have a special division of baitul maal in the management of zakat, infaq and social funds. Furthermore, in facing challenges in collecting zakat, infaq and social funds, the BMT Dana Akhirat Arjasari Cooperative must maximize its opportunities and strengths, such as having many members with various professions, establishing good relations with village officials, mosque and pesantren administrators, the amount of funds Zakat, infaq and social funds are quite large every year, there are educational scholarships for children of members who excel, establish good relations with DISKOP and UKM Kab. Bandung by DEKOPINDA.